Review of Properties and Analytical Methods for the Determination of Norfloxacin - Chierentin, Lucas [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2016)
The first-generation quinolones have their greatest potency against Gram-negative bacteria, but newly developed molecules have exhibited increased potency against Gram-positive bacteria, and existing agents are available with additional activity against anaerobic microorganisms. Norfloxacin is a broad-spectrum antimicrobial fluoroquinolone used against Gram-positive and Gram-negative organisms (aerobic organisms). There are different analytical methods available to determine norfloxacin applied in quality control of this medicine in order to ensure its effectiveness and safety. The authors present an overview of the fourth generation of quinolones, followed by the properties, applications, and analytical methods of norfloxacin. These results show several existing analytical techniques that are flexible and broad-based methods of analysis in different matrices. This article focuses on bionalytical and pharmaceutical quality-control applications, such as thin-layer chromatography, microbiological assay, spectrophotometry, capillary electrophoresis (CE), and high-performance liquid chromatography (HPLC).
Keywords: Analytical methods; norfloxacin; fluoroquinolones; quality control; pharmacokinetics